Study of the carrying capacity of the Brantas River to the Porong River based on the distribution of atrazine pollutant from agricultural land with the application of a geographical information system (GIS) - Nurina Fitriani, Nurina Fitriani; Diah Aldina Khairunnisa, Diah Aldina Khairunnisa; Bariq Athilla Dermawan, Bariq Athilla Dermawan; Febri Eko Wahyudianto, Febri Eko Wahyudianto; Radin Mohamed, Radin Maya Saphira; Eddy Setiadi Soedjono, Eddy Setiadi Soedjono; Wahid Dianbudiyanto, Wahid Dianbudiyanto; Dwi Ratri Mitha Isnadina, Dwi Ratri Mitha Isnadina (springer, 2024)
Agricultural land dominates Brantas River watershed, so it is potentially polluted due to excessive use of agrochemicals. This study aims to calculate the carrying capacity of atrazine and map its distribution from Brantas to Porong River. Carrying capacity is calculated using mass balance approach based on the Decree of the Minister of Environment Number 110 of 2003. Mapping is done using IDW interpolation on ArcGIS Pro. There are 19 sampling points in the upstream-middle part and 21 points in the middle-downstream part. All sample points had atrazine levels exceeding the quality standard of 0.002 mg.L−1. The carrying capacity was calculated to be −368,820.16 kg.day−1 in the upstream-middle part and −63,382.24 kg.day−1 in the middle-downstream part due to the APL being greater than MPL. Based on the mapping results, atrazine concentrations in the upstream-middle section have the highest range in Segment 1 (4.0–11.6 mg.L−1) and in the middledownstream section in Segment A (11.4–17.6 mg.L−1).